Thursday

December 18, 2014

December 18, 2014

Posted by **Sasha** on Wednesday, December 15, 2010 at 11:28pm.

- calculus -
**Reiny**, Thursday, December 16, 2010 at 12:34am3x^2 + 4y dy/dx + 3xdy/dx + 3y = 0

dy/dx(4y+3x) = -3x^2 - 3y

dy/dx = (-3x^2 - 3y)/(4y+3x)

at (1,1) dy/dx = (-3-3)/(4+3) = -6/7

y-1 = (-6/7)(x-1

times 7

7y - 7 = -6(x-1)

7y - 7 = -6x + 6

6x + 7y = 13

**Answer this Question**

**Related Questions**

Calculus - Please help this is due tomorrow and I dont know how to Ive missed a ...

Calculus - Find the equation of the tangent line to the curve x^(3)+3xy+y^(3)=1 ...

calculus - Consider the curve defined by 2y^3+6X^2(y)- 12x^2 +6y=1 . a. Show ...

Calculus - Consider line segments which are tangent to a point on the right ...

Calculus - If F(x)=x^3−7x+5, use the limit definition of the derivative to...

Calculus AP - implicit differentiation Find the slope of the tangent line to ...

Calculus AP need help! - i dont know how or what to starts Find the slope of the...

calculus - Consider line segments which are tangent to a point on the right half...

Calculus. I need help! - HARDER PARTS WAS 3(x^2+y^2)^2=26(y^2+y^2) Find the ...

COLLEGE CALCULUS. - Use implicit differentiation to find the equation of the ...